The difference in proliferation assessed by AgNOR between giant cell lesions of the jaw and giant cell tumor of long bones (Mustansiria Dental Journal, 2018)
The difference in proliferation assessed by AgNORbetween giant cell lesions of the jaw and giant celltumor of long bones